2010
DOI: 10.1002/bjs.7227
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of Chinese herbal medications to reduce wound complications after mastectomy for breast carcinoma

Abstract: Anisodamine and S. miltiorrhiza were both effective in reducing skin flap ischaemia and necrosis after mastectomy, although anisodamine was associated with a higher rate of adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Danshen is a very commonly used Chinese herbal medicine for cardiovascular conditions [ 180 , 181 , 182 ]. In a clinical trial, this herbal medicine has been shown to be effective in reducing skin flap ischemia and necrosis after mastectomy [ 183 ]. The effects of antiplatelet aggregation of Danshen have been reported from a number of investigations.…”
Section: Resultsmentioning
confidence: 99%
“…Danshen is a very commonly used Chinese herbal medicine for cardiovascular conditions [ 180 , 181 , 182 ]. In a clinical trial, this herbal medicine has been shown to be effective in reducing skin flap ischemia and necrosis after mastectomy [ 183 ]. The effects of antiplatelet aggregation of Danshen have been reported from a number of investigations.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Sui and Zhang [33] reported that there were a number of participants with xerostomia for both groups injected with anisodamine. Also, two other studies [20, 21] that administered anisodamine for their pharmacopuncture group reported AEs such as xerostomia along with hot flashes and blurred vision, which are all commonly known AEs of anisodamine itself [48, 49]. This can be suggesting that those AEs may be caused by the drug itself and not by the modality of pharmacopuncture.…”
Section: Discussionmentioning
confidence: 99%
“…One study indicated that injection of S. miltiorrhiza and ligustrazine can effectively reduce myocardial damage in patients with severe burns [19]. Animal studies also indicate that S. miltiorrhiza enhances the wound healing process [20,21]. Randomized clinical trial of S. miltiorrhiza suggested that it is effective in reducing skin flap ischaemia necrosis after mastectomy [20].…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies also indicate that S. miltiorrhiza enhances the wound healing process [20,21]. Randomized clinical trial of S. miltiorrhiza suggested that it is effective in reducing skin flap ischaemia necrosis after mastectomy [20]. S. miltiorrhiza can stimulate the cell proliferation and it has the potential to be used for wounding healing or cosmetic treatment [22].…”
Section: Discussionmentioning
confidence: 99%